Correlation of Body Shape Concern and Anxiety Severity among Sales Women in Medan - Efffendy, Elmeida; Mardhiyah, Sarah A.; Hasanuddin, Nabilah A.; Gustirani, Shela (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Body image was recognized as one of the major concerns of emerging adults as well as adolescents. The resulting dissatisfaction with body image has become a more universal phenomenon. Past research in body image has generally focused on women interested in the achievement of thin ideas. Some findings suggest that problems with body image may underlie at least some social anxiety Methods: A Cross Sectional study using 135 sales women was conducted by self-reported measures (questionnaire). Body image dissatisfaction was measured using Body shape questionnaire-34, anxiety score using Hospital Anxiety and Depression Scale ( HADS). We use Kolmogorov Smirnov test to assess the normality of the data , and Pearson correlation test to assess the correlation between BSQ-34 and HADS. Results: The average age of our respondents were 23.57+5.657 and majority of them were graduated from high school (n=97, 72%) and are not married yet (n=109, 81%). Less than half admitted to have already worked for more than a year and we also found that most sales women in our study earned less than minimum standard wage a month (n=103, 76%). We found that all of our respondents showed BSQ-score of above 81 (82.14 + 4.530) indicating that all are slightly preoccupied with body shape concern. We also found that all respondents showed borderline anxiety score with average score of 8.20 + 3.256. Pearson correlation test showed that there is significant positive moderate strength correlation between body shape concern and anxiety severity (r = 0.413, p = 0.002). Discussion: This study revealed a significant positive relationship between the body shape concern and anxiety among saleswoman; our hypothesis was confirmed.